“Hamsun’s Liminality” : In Wonderland as Counter-Discourse - El Samad, Soha (Nordlit, 2020)
This study seeks to establish the extent to which In Wonderland is a cultural hybridity discourse and a writing-back to Euro-American travelogues. In this ‘different’ travelogue, Hamsun’s voice cuts through the borderlands of the Russian colonized Caucasus region to reveal contempt for acquired culture and a rejection of global uniform identities in a manner that accords with Homi Bhabha’s concept of ‘hybridity.’ While keeping in mind Hamsun’s undisputed parodic style, this postcolonial reading claims that mimicry, as applied by Hamsun, is a practical demonstration of Bhabha’s theory that reflects his propensity to destabilize the West’s monolithic stance as regards the Orient. It therefore reveals the manner in which his supposedly colonial discourse exposes the discriminatory nature of colonial dominance. Within this context, Hamsun has become a cultural hybrid who refuses to imitate conventional European travel narratives or follow in their differentiating paths. On the whole, the basic argument is that Hamsun’s travelogue which invariably asserts, subverts and removes boundaries, does not endorse Orientalism neither in its romantic nor in its subservient form.